Retention in Construction Contracts: Legal Analysis and Implementation Practices in Indonesia - Dina Silviana; Sarwono Hardjomuljadi; Sami’an Sami’an; Anik Kunantiyorini (International Journal Labs, 2025)
Retention is a mechanism for withholding part of payments in construction contracts that is used to ensure the fulfillment of work maintenance obligations. In practice, retention often raises disputes, especially regarding late payments, detention without legitimate reasons, or unclear terms for release of retention. This study analyzes the legal position of retention, the legal basis that requires its payment, and the implications of default when retention is still withheld after the work is declared completed through the Final Hand Over (FHO). The research uses a literature study method on the Civil Code, the Construction Services Law, the FIDIC Red Book, procurement document standards, and contract law literature. The results of the study show that retention is a legal part of a contractual agreement that is subject to the principle of pacta sunt servanda based on Article 1338 of the Civil Code. Retention detention without a legal basis after the issuance of the FHO constitutes a default, which results in the obligation to pay retention along with compensation in accordance with Article 1243 of the Civil Code. The research concludes that the retention payment is an absolute obligation that must be fulfilled and its violation entitles the Contractor to demand performance and compensation.